The Influence of Reward Systems and Employee Development on Employee Performance: A Case Study of the World Trade Centre Kuala Lumpur (WTCKL) - Irmohizam, Ibrahim (2023)
This study focuses on the elements that influence of reward system (intrinsic and extrinsic) and employee development on employee performance at World Trade Centre, Kuala Lumpur. The purpose of this study is to investigate the relationship between feedback, opportunity of professional growth, self-esteem, pay, benefit, promotion and employee performance through leadership and recognition, organizational policies and team relations in the work environment. This study applies quantitative approaches. The data was collected from an interview session with the Corporate Director of WTCKL and secondary data, while a questionnaire survey was distributed among 169 employees, which were selected through convenience sampling. To determine the link between the variables, the data was examined using the regression analysis. The investigation revealed the r-square value indicates 62.1% of the variance in the dependent variable (employee performance) can be explained by the independent variable (intrinsic, extrinsic rewards and employee development). The Cronbach’s Alpha for intrinsic rewards is 89.7%, which is very good. Extrinsic rewards are 89.2%, which is considered very well then for employee development with 91.5% which are very excellent. Meanwhile, the Cronbach’s Alpha for employee performance is good, with a value of 74.8%. The correlation between intrinsic rewards and employee performance is 0.692 and it is indicated as a modest correlation. The employee development have the modest correlate with .621 and while for extrinsic rewards have the same modest positive impact on employee performance with a value of 0.484. The Pearson correlation analysis show that both intrinsic, extrinsic rewards and employee development have a significant impact on employee performance. Hence, H1, H2 and H3 are supported.